Estimating the potential impact of COVID-19-related disruptions on HIV incidence and mortality among men who have sex with men in the United States: a modelling study. - Mitchell,KM; Dimitrov,D; Silhol,R; Geidelberg,L; Moore,M; Liu,A; Beyrer,C; Mayer,KH; Baral,S; Boily,M-C (Cold Spring Harbor Laboratory, 2020)
Background: During the COVID-19 pandemic, gay and other men who have sex with men (MSM) in the United States (US) report similar or fewer sexual partners and reduced HIV testing and care access. Pre-exposure prophylaxis (PrEP) use has declined. We estimated the potential impact of COVID-19 on HIV incidence and mortality among US MSM. Methods: We used a calibrated HIV transmission model for MSM in Baltimore, Maryland, and available data on COVID-19-related disruptions to predict impacts of data-driven reductions in sexual partners(0%,25%,50%), condom use(5%), HIV testing(20%), viral suppression(10%), PrEP initiations(72%), PrEP use(9%) and ART initiations(50%), exploring different disruption durations and magnitudes. We estimated the median (95% credible interval) change in cumulative new HIV infections and deaths among MSM over one and five years, compared with a scenario without COVID-19-related disruptions. Findings: A six-month 25% reduction in sexual partners among Baltimore MSM, without HIV service changes, could reduce new HIV infections by 12·2%(11·7,12·8%) and 3·0%(2·6,3·4%) over one and five years, respectively. In the absence of changes in sexual behaviour, the six-month data-driven disruptions to condom use, testing, viral suppression, PrEP initiations, PrEP use and ART initiations combined were predicted to increase new HIV infections by 10·5%(5·8,16·5%) over one year, and by 3·5%(2·1,5·4%) over five years. A 25% reduction in partnerships offsets the negative impact of these combined service disruptions on new HIV infections (overall reduction 3·9%(-1·0,7·4%), 0·0%(-1·4,0·9%) over one, five years, respectively), but not on HIV deaths (corresponding increases 11·0%(6·2,17·7%), 2·6%(1·5,4·3%)). The predicted impacts of reductions in partnerships or viral suppression doubled if they lasted 12